2011
DOI: 10.1063/1.3629983
|View full text |Cite
|
Sign up to set email alerts
|

Laser wake-field acceleration in pre-formed plasma channel created by pre-pulse pedestal of terawatt laser pulse

Abstract: The role of nanosecond duration pre-pulse pedestal (Amplified Spontaneous Emission (ASE) pre-pulse) in the propagation of 45 fs, 4 TW Ti:Sapphire laser pulse through a helium gas jet target has been investigated. We observed that the pre-pulse pedestal of about 1 ns duration and intensity 3 × 1012 W/cm2 creates pre-formed plasma with optical guiding channel like structure in the gas-jet at density around 3 × 1019 cm−3. Guiding of the 45 fs laser pulse (IL = 3 × 1018 W/cm2) in the pre-formed plasma channel, ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Simultaneous measurement of nonlinear Thomson side-scattering images showed smooth and stable selfguiding channels with length 490 μm. Increasing the level of prepulse reduced the stability of the electron beam as observed in our earlier investigations [14].…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Simultaneous measurement of nonlinear Thomson side-scattering images showed smooth and stable selfguiding channels with length 490 μm. Increasing the level of prepulse reduced the stability of the electron beam as observed in our earlier investigations [14].…”
supporting
confidence: 73%
“…Although the electron energy in the present study is relatively less compared to Ref. [14], a low level of prepulse in the present study is found to contribute to improvement in the stability of the electron beam parameters as observed in an earlier study [23].…”
Section: High-quality Stable Electron Beams …supporting
confidence: 54%
See 1 more Smart Citation
“…The ASE pre-pulse and replica pulse contrast ratios were measured using a fast photo-diode with a 0.8 ns rise time on a 500 MHz digital oscilloscope. The typical ASE pre-pulse pedestals for two different switching times of the Pockels cell were similar to those in [18]. The duration of the ASE pre-pulse pedestal was controlled by changing the switching-on time of the high voltage pulse on the Pockels cell of the pulse cleaner (located after the regenerative amplifier) in the Ti:sapphire laser system.…”
Section: Methodsmentioning
confidence: 69%
“…The threshold can be altered by changing the polarization angle of the laser pulse, [42] and it can increase the maximum energy of electrons. [40,[43][44][45][46][47][48] Therefore, the direct laser acceleration of electrons in under-dense density plasma channel has attracted much attention. However, the coupling characteristics between chirped laser pulse and plasma channel and its effect on electron acceleration are still unclear.…”
Section: Introductionmentioning
confidence: 99%